High-throughput SPE-LC-MS/MS method for determination of indapamide in human serum - Natalija Nakov; Kristina Mladenovska; Dimche Zafirov; Aleksandar Dimovski; Rumenka Petkovska; Aneta Dimitrovska; Zoran Kavrakovski (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2013)
Simple, automated SPE procedure combined with fast LC-MS/MS chromatographic separation resulted in obtaining high-throughput LC-MS/MS method for determination of indapamide in serum. The SPE procedure was performed on polymeric mixed-mode sorbent and the analytes were quantitated using electrospray ionization in positive mode. The recovery of indapamide and internal standard were 89.25- 90.36% and 79.10%, respectively. Experimentally it was confirmed that the matrix effect had a negligible effect of ionization efficiency. The validation data showed that the proposed method provides accurate and reproducible results in range of 0.50-50 ng/mL. In addition, a comparison was made between the method for determination of indapamide in serum and in blood (develop in our previously work) regarding the extraction procedure and matrix effect.